Perilaku Self-Harm pada Remaja Broken Home Pengguna Sosial Media di Karawang: Peran Adverse Childhood Experiences dan Dukungan Sosial - Dewi Anggraeni; Cempaka Putrie Dimala; Haryanti Mustika (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the effect of adverse childhood experiencess and social support on self-harm behavior among adolescents from broken homes. The study sample consisted of 204 participants, including 65 males and 139 females aged between 13 and 21 years old residing in Karawang Regency. The sampling technique used was convenience sampling, which involves selecting participants based on their availability and ease of access. Data collection was conducted using a quantitative approach with three main instruments: the Self-harm Inventory (SHI) to measure self-harm behavior, the Adverse childhood experiences Questionnaire (ACE-Q) to measure adverse childhood experiencess, and the Social Provisions Scale (SPS) to measure perceptions of social support. The data obtained were analyzed using multiple regression analysis. The results of the analysis indicated that adverse childhood experiencess significantly influenced self-harm behavior (significance value = 0.00; p < 0.05). However, social support did not have a significant influence on self-harm behavior (significance value = 0.187; p > 0.05). These findings indicate that adverse childhood experiencess play an important role in the development of self-harm behavior, while social support may not be sufficient to reduce the tendency toward self-harm behavior among adolescents from broken homes in Karawang.